2001
DOI: 10.1038/ncb1101-1001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore dynein: its dynamics and role in the transport of the Rough deal checkpoint protein

Abstract: We describe the dynamics of kinetochore dynein-dynactin in living Drosophila embryos and examine the effect of mutant dynein on the metaphase checkpoint. A functional conjugate of dynamitin with green fluorescent protein accumulates rapidly at prometaphase kinetochores, and subsequently migrates off kinetochores towards the poles during late prometaphase and metaphase. This behaviour is seen for several metaphase checkpoint proteins, including Rough deal (Rod). In neuroblasts, hypomorphic dynein mutants accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
225
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(257 citation statements)
references
References 37 publications
23
225
1
Order By: Relevance
“…However, it is likely that an active mechanism is involved in relieving SAC signaling because anaphase begins within minutes after the last mis-aligned chromosome congresses to the metaphase plate [Rieder et al, 1994] or after laser ablation of the last unattached kinetochore [Rieder et al, 1995]. Such a mechanism may involve the active displacement of spindle checkpoint proteins from the kinetochore once a stable attachment to the spindle is established [Wojcik et al, 2001]. Following attachment of mammalian kinetochores to the spindle and chromosome alignment, the kinetochore-localized dynein/dynactin complex transports the checkpoint proteins Mad2, BubR1, and ROD away from kinetochores along the spindle to the spindle poles [Howell et al, 2001;Wojcik et al, 2001].…”
Section: Silencing the Spindle Checkpointmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is likely that an active mechanism is involved in relieving SAC signaling because anaphase begins within minutes after the last mis-aligned chromosome congresses to the metaphase plate [Rieder et al, 1994] or after laser ablation of the last unattached kinetochore [Rieder et al, 1995]. Such a mechanism may involve the active displacement of spindle checkpoint proteins from the kinetochore once a stable attachment to the spindle is established [Wojcik et al, 2001]. Following attachment of mammalian kinetochores to the spindle and chromosome alignment, the kinetochore-localized dynein/dynactin complex transports the checkpoint proteins Mad2, BubR1, and ROD away from kinetochores along the spindle to the spindle poles [Howell et al, 2001;Wojcik et al, 2001].…”
Section: Silencing the Spindle Checkpointmentioning
confidence: 99%
“…Such a mechanism may involve the active displacement of spindle checkpoint proteins from the kinetochore once a stable attachment to the spindle is established [Wojcik et al, 2001]. Following attachment of mammalian kinetochores to the spindle and chromosome alignment, the kinetochore-localized dynein/dynactin complex transports the checkpoint proteins Mad2, BubR1, and ROD away from kinetochores along the spindle to the spindle poles [Howell et al, 2001;Wojcik et al, 2001]. Mutation of dynein [Wojcik et al, 2001] or inhibition of dynein/dynactin activity [Howell et al, 2001] promotes a SAC-dependent metaphase arrest.…”
Section: Silencing the Spindle Checkpointmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, hypomorphic dynein mutant neuroblasts in Drosophila are known to accumulate in prometaphase/metaphase with a high frequency of spindle defects and p50 dynamitin has been identified in the cell cortex of syncytial embryos [98]. In another study, Savoian and colleagues used zw10 and rod Drosophila mutant spermatocytes to specifically perturb dynein localization at kinetochores [99,100] and showed that anaphase chromosome motion to the poles was severely affected in those mutants.…”
Section: Kinetochore Dyneinmentioning
confidence: 99%
“…These results support that microtubule endon attachment, rather than dynein motor activity at kinetochores is essential for chromosome movement to the poles. It should be emphasized that dynein levels at kinetochores become reduced as microtubules attach and are barely detectable as cells enter anaphase [98,110]. Recently, it was shown that phosphorylation of Threonine 89 on dynein intermediate chain directs binding to ZW10 and that microtubule attachment induces dynein dephosphorylation to undetectable levels after metaphase chromosome alignment [111].…”
Section: Kinetochore Dyneinmentioning
confidence: 99%